1996
DOI: 10.1177/0266242696142004
|View full text |Cite
|
Sign up to set email alerts
|

Working Capital and Financial Management Practices in the Small Firm Sector

Abstract: MICHAELJ. PEEL IS A LECTURER IN accountancy and finance at Cardiff Business School, University of Wales, and Nicholas Wilson is Professor of Credit Management at the University of Bradford, England. Very little research has been conducted on the capital budgeting and working capital practices of small firms. The purpose of this paper is to present the results of a preliminary study on the working capital and financial management practices of a sample of small firms located in the north of England. In general, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
161
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(180 citation statements)
references
References 5 publications
12
161
0
7
Order By: Relevance
“…If a small company has the same potential consumers as large enterprises based on the 5Cs criteria, then the small companies will have the opportunity to shorten the billing period of receivables. Peel and Wilson (1996) in Karina (2012) state that the big companies with great liquidity can pay their customers in a timely manner. Damodaran (2001) in Karina (2012) also explains that the volume of inventory can be determined by product availability, cost and the production lines of the company.…”
Section: Results and Analysismentioning
confidence: 99%
“…If a small company has the same potential consumers as large enterprises based on the 5Cs criteria, then the small companies will have the opportunity to shorten the billing period of receivables. Peel and Wilson (1996) in Karina (2012) state that the big companies with great liquidity can pay their customers in a timely manner. Damodaran (2001) in Karina (2012) also explains that the volume of inventory can be determined by product availability, cost and the production lines of the company.…”
Section: Results and Analysismentioning
confidence: 99%
“…and to the debt capital market (bank debt, structured finance, syndicated loans, etc. ), as highlighted by various studies [19][20][21][22][23]. Generally speaking, for the financing of investments in property, plants and equipment, the firms of the sector use, in addition to equity capital (E), long-term bank loans and real estate leasing articulated generally in a technical form of mortgages with a guarantee on real estate property and, less frequently, articulated in an unsecured form; in this last case, durations are reduced and often collateral security with a pledge or guarantee of signature is requested and often given by members or credit guarantee consortia.…”
Section: Overview Of Firm Characteristics In the Tomato Sectormentioning
confidence: 93%
“…NWC quantifies the net resources generated (NWC < 0) or absorbed (NWCt > 0) by the working capital management cycle (Love et al, 2007;Baños-Caballero et al, 2013). It has been shown that the management of working capital is particularly relevant for small firms (Arcelus and Srinivasan, 1993;Saccurato, 1994;Chittenden et al, 2000;Kieschnick et al, 2013), as these enterprises have limited access to the capital market in the medium term and then tend to finance fixed asset investments with debt maturing within twelve months and show rates of default higher than those of large firms (Grablowsky, 1976;Dunn and Cheatham, 1993;Peel and Wilson, 1996;Gray et al, 2006;Molina and Preeve, 2009). This is true even in recent years in Italy (Modina and Pietrovito, 2014;Gordini, 2014).…”
Section: Balance Sheet Analysis Approachmentioning
confidence: 99%
“…and to financial debt (bank debt, structured finance, syndicated loans, etc. ), as shown by several studies (Grablowsky, 1976;Dunn and Cheatham, 1993;Peel and Wilson, 1996;Molina and Preeve, 2009;Woods et al, 2014) highlighting the need for analysis of economic feasibility and financial projects even in the case of aquaculture (Molinos-Senante et al, 2010;Kaiser et al, 2010;Naziri, 2011;Kim and Lipton, 2011;Shamshak, 2011;Hadelan et al, 2012;Kim et al, 2012;Vilela et al, 2013;Emdad Haque et al, 2015).…”
Section: Introductionmentioning
confidence: 99%